Probing polarization-tunable sub-terahertz spin pumping in bimodal α-Fe2O3/Pt - Gregory Fritjofson; Atul Regmi; Jacob Hanson-Flores; Justin Michel; Junyu Tang; Fengyuan Yang; Ran Cheng; Enrique Del Barco (npj Spintronics)
Abstract Hematite (α-Fe2O3) is an insulating antiferromagnet possessing a room temperature canted phase induced by the super-exchange Dzyaloshinskii-Moriya Interaction (DMI), resulting in enhanced spin pumping and spin transport over uniaxial antiferromagnets. In this work we resonantly excite the quasi-ferromagnetic (acoustic) and purely antiferromagnetic (optical) spin-dynamical modes in bulk and thin-film heterostructures of α-Fe2O3/Pt at room temperature, inducing inverse-spin-Hall-voltages up to 255 GHz. Following recent measurements of optical-mode spin-pumping in α-Fe2O3, we observe a novel and exotic microwave polarization mapping along with amplified spin-charge conversion in the optical branch and discuss the implications of layer thickness on acoustic and optical spin-modes. The results provide a deeper understanding of spin-wave selection rules for canted antiferromagnets and their potential use in nanoscale terahertz spintronics.